A newly discovered Lnc-PDZD7-3 increased metastatic and proliferative potential of lung adenocarcinoma cells via modulating FN1/fibronectin signaling - Zhang, Guodong; Zhang, Jianbo; Yu, Fachang; Hao, Xiaohe (Frontiers in Genetics, 2025)
The global burden of lung adenocarcinoma (LUAD) has been on the rise, making it among the leading contributor to cancer-related deaths. Long non-coding RNA (lncRNA) are implicated in the initiation and progression of LUAD. To date, the mechanism by which lncRNA participate in LUAD are not clearly characterized. Here, we investigated the role of the newly-discovered Lnc-PDZD7-3 in the development of LUAD. Results revealed downregulation of Lnc-PDZD7-3 in human normal lung tissues and upregulation in LUAD tissues from the TCGA (The Cancer Genome Atlas) databases. Excessive expression of Lnc-PDZD7-3 promotes occurrence of distant metastasis. Lnc-PDZD7-3 knockdown suppressed the proliferative and viability potential of cells, as well enhanced apoptosis and inhibited the migratory activity of LUAD cells. Notably, expression levels of MMP9, Vimentin, Twist, Fibronectin, and MMP2 in LUAD cells were downregulated markedly except for snail following Lnc-PDZD7-3 knockdown. Through rescue experiments, we confirmed that Lnc-PDZD7-3 enhanced LUAD development by activating FN1/fibronectin signaling. Meanwhile, we also identified that Lnc-PDZD7-3 was localized in cytoplasm and nucleus segments of LUAD cells by FISH technology. In summary, this study implicates Lnc-PDZD7-3 in the pathomechanisms of LUAD via the FN1/fibronectin signaling, suggesting it may be diagnostic biomarker and therapeutic targets of LUAD.